Psychological Context of Managerial Staff Compensation – Polish Experiences - MOCZYDŁOWSKA Joanna (Journal of Economic and Social Development (Varaždin), 2018)
The article is meant to become part of the scientific discussion concerning the psychological foundations shaping the compensation system and transparency of managerial staff’s salaries. It is founded on a scientifically proven assumption that in respect to salaries the employees’ assessment, including management staff, of their attractiveness is contingent on numerous factors with the most important ones being psychological in character. Through analysis the article aims to identify managerial staff’s opinions regarding the psychological aspects of the remuneration system including: integrity, justice, adequacy and transparency. To achieve this goal the author used a questionnaire which was administered to 120 representatives of middle and senior managerial staff working within the corporate sector functioning in Poland. The present study should be considered to be a pilot study. It was determined that sex was one of the variables which meaningfully influenced the psychological aspects of evaluating a remuneration system. In general, most male managers gauge their salary as satisfying whereas female managers who show satisfaction with their salary constitute less than half of the study sample. Clearly, therefore, women more often than men considered their salary to be unsatisfactory or average. In contrast to their male counterpart’s female study participants more often described their salary as fair if it was based on such factors as time needed for job completion and mental strain. Managers taking part in the study, regardless of gender, specified difficulty, the degree of responsibility connected with their job and results achieved by a team which they managed as having the greatest influence on their perception of their salary as fair. Majority of managers expect their salary not be dependent upon the financial success of the company as a whole. Additionally, they express acceptance for differences within salaries of managers working for the same organization and their direct correlation to individual accomplishment. Most management staff support the idea that salary amounts remain undisclosed but advocate transparency in the way salaries are structured.